Effect of Using Different Substrate and Supplemented Materials on Paddy Mushrooms (Volvariella volvacea) Cultivation in Plastic Baskets - PHOMLASABOUD, Khantavanh; SIBOUNNAVONG, Phoutthasone (Souphanouvong University Journal Multidisciplinary Research and Development, 2017)
The aim of the study was to investigate the suitability of supplements and substrates for paddy mushroom cultivation. In particular, the chemical composition of the substrates and mushroom products were analyzed, the economic value assessed and a cost benefit analysis conducted. The experiment was set up as Completely Randomized Design (CRD) with two factors. The first factor (A) is substrates (rice straw, finished mushroom spawn, dried banana stem, and dried maize stem) while the second factor (B) is supplements (no supplements (control), or addition of either water hyacinth leaves or fresh banana stem pieces). There were 12 Treatments as a1b1(rice straw+ no supplements (control), a1b2(rice straw + water hyacinth leaves), a1b3(rice straw + fresh banana stem pieces), a2b1(finished mushroom spawn + no supplements (control)), a2b2(finished mushroom spawn + water hyacinth leaves), a2b3(finished mushroom spawn+ fresh banana stem pieces), a3b1(dried banana stem+no supplements (control)), a3b2(dried banana stem+ water hyacinth leaves), a3b3(dried banana stem + fresh banana stem pieces),, a4b1(dried maize stem + no supplements (control)), a4b2(dried maize stem + water hyacinth leaves), and a4b3(dried maize stem + fresh banana stem pieces). The result show that both factors significantly yield and number of mushrooms harvested (P<0.05). Rice straw substrate supplemented with water hyacinth (a1b2) gave the highest yield at 656.5g per plot (experimental unit) when compared to other substrate and supplemented followed by a1b1, a3b2, a4b2, a1b3, a3b3, a3b1, a2b2, a4b3, a4b1, a2b1 and a2b3 at 527.80,516.50, 381.30, 350.30, 348.70, 345.70, 285.50, 220.80, 168.00 and 167.50 g per basket respectively. For the number of mushrooms harvested it was also a1b2 that gave the highest numbers with 48.75 mushrooms per plot followed by a1b1; a3b2; a3b1; a4b2; a1b3; a3b3; a2b2; a4b3; a4b1; a2b3 and a2b1 at 36.75; 35.25; 28.50; 25.25; 24.25; 20.75; 19.50; 18.75; 14.50; 10.25 and 8.75 mushrooms per basket respectively. However, there is no significant effect on fresh weight and diameter of individual paddy mushrooms. It was found that the chemical composition of the substrates differed significantly (P<0.05) with dried maize stem containing highest levels of nitrogen when compared to rice straw, dried banana stem, and finished mushroom spawn with 1.12, 0.63,​​ 0.49 and 0.28 % respectively. Water hyacinth (1.26%) contain higher a mounts of nitrogen compared to banana stem (0.49%).The cost benefit analysis for paddy mushroom cultivation. respectively. This research finding indicate that using rice straw as the substrate and supplemented with water hyacinth is the most suitable method for paddy mushroom cultivation in term of getting high yield and economic value and cost benefit.